2013
DOI: 10.1007/s00296-013-2769-1
|View full text |Cite
|
Sign up to set email alerts
|

Punctal plugs versus artificial tears for treating primary Sjögren’s syndrome with keratoconjunctivitis SICCA: a comparative observation of their effects on visual function

Abstract: To compare the effects of treatment with punctal plugs versus artificial tears on visual function for primary Sjögren's syndrome with dry eye. Forty-two eyes of 42 patients with primary Sjögren's syndrome were enrolled and were allocated randomly into artificial tears (AT) group and punctal plugs (PP) group. Ocular Surface Disease Index (OSDI) was used, and fluorescent staining for tear film break-up time (BUT), the Schirmer test I (STI) and contrast sensitivity was performed before treatment and was repeated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
58
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(63 citation statements)
references
References 15 publications
0
58
0
5
Order By: Relevance
“…The number of participants with pSS in the studies ranged from n = 42 [33] to n = 18 [29]. All studies recruited both males and females, but the numbers of males recruited to each study were low and ranged from n = 1 [30] to n = 4 [33], which is representative of the pSS population. One study [30] included participants diagnosed with pSS according to the Copenhagen [34] and San Diego Criteria [35] and the proposed European Community Study Group Criteria [36].…”
Section: Participantsmentioning
confidence: 99%
See 4 more Smart Citations
“…The number of participants with pSS in the studies ranged from n = 42 [33] to n = 18 [29]. All studies recruited both males and females, but the numbers of males recruited to each study were low and ranged from n = 1 [30] to n = 4 [33], which is representative of the pSS population. One study [30] included participants diagnosed with pSS according to the Copenhagen [34] and San Diego Criteria [35] and the proposed European Community Study Group Criteria [36].…”
Section: Participantsmentioning
confidence: 99%
“…One study [30] included participants diagnosed with pSS according to the Copenhagen [34] and San Diego Criteria [35] and the proposed European Community Study Group Criteria [36]. The Qiu et al [33] study reported that participants were diagnosed according to the American European Consensus Criteria [3]. Mansour et al [32] recruited participants diagnosed according to the European Criteria [36].…”
Section: Participantsmentioning
confidence: 99%
See 3 more Smart Citations